Development of an onboard system for flight data collection of a small-scale UAV helicopter - Taha, Zahari; Tang, Y.R.; Yap, K.C. (Elsevier, 2011)
This paper presents the development of an onboard system of a small-scale Unmanned Aerial Vehicle (UAV) helicopter. Both the hardware and software parts of the system have been developed. In the hardware part, several components are carefully selected or custom made for five separate systems including PC/104 computer system, sensor system, telemetry system, power system and bypass circuit system. The constructed hardware exhibits low weight, small size, anti-vibration, low power consumption, and easy interfacing. In the software part, the onboard software periodically manipulates the hardware components in a specified order. In every cycle, the system collects data from an Inertial Measurement Unit (IMU) and a Counter/Timer (C/T) card, and records them in a Compact Flash (CF) card as well as sends them to a ground station. The onboard system has been tested in actual flight, and the reliability and feasibility are evaluated. The results are plotted and analyses have shown that the collected data is sufficiently accurate for modeling the helicopter.